2011
DOI: 10.1021/ol202924s
|View full text |Cite
|
Sign up to set email alerts
|

Pyridines from Azabicyclo[3.2.0]hept-2-en-4-ones through a Proposed Azacyclopentadienone

Abstract: Pyridines have been formed by heating azabicyclo[3.2.0]hept-2-en-4-ones in toluene. The generation of a 3-azacyclopentadienone intermediate via a [2 þ 2]-cycloreversion is proposed as the key step. A DielsÀAlder reaction of a styrene, extrusion of carbon monoxide, and loss of hydrogen then gives the pyridine. The process parallels the well-known synthesis of benzenes from cyclopentadienones. The azabicyclo[3.2.0]hept-2-en-4-ones were synthesized from the reaction between readily available cyclopropenones and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…2-Methylthio-4-(naphth-2-yl)-1-azetine 5 (Scheme 1) has been synthesized by us before [9,10] and used in cycloaddition reactions. Previously, the 1-azetine was obtained by alkylation of the readily available [9,10] thiolactam 7, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2-Methylthio-4-(naphth-2-yl)-1-azetine 5 (Scheme 1) has been synthesized by us before [9,10] and used in cycloaddition reactions. Previously, the 1-azetine was obtained by alkylation of the readily available [9,10] thiolactam 7, as shown in Scheme 1.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, the 1-azetine was obtained by alkylation of the readily available [9,10] thiolactam 7, as shown in Scheme 1. When this reaction mixture is worked up and purified immediately, the 1-azetine is the major product, as already reported [9,10].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25 Nonetheless, we have shown that 1-azetines are able to act as precursors for the synthesis of benzoisoquinolines, 21 homotropane related heterocycles 22 and pyridines 23 via a formal [3+2]-cycloaddition reaction with cyclopropenones (which act as all-carbon 1,3-dipole equivalents) as well as acting as dipolarophiles for the synthesis of 1,2,4-oxadiazoles 24 via reaction with nitrile oxides. As a result of these successes, and given our interest in the β-sultam nucleus, we wished to explore the chemistry of the unsaturated β-sultam system, the thiazete 1,1-dioxide (4).…”
Section: Figure 1 Heterocycles Of Interest In This Workmentioning
confidence: 99%